Examination of bacterial populations in salt, salted hides, soaked hides and SOAK liquors - (:unkn) unknown (My University, 2010)
This study was performed to evaluate the efficiency of salt curing and soaking methods containing antibacterial agents. The bacteria adversely affecting hide quality because of hide preservation method and soaking process were examined in salt (n=40), salted hide (n=36), soaked hide (n=34) and soak liquor (n=19) samples obtained from different tanneries in Leather Organized Tannery Region, Tuzla-i̇stanbul, Turkiye. Most of the hides examined in this study (83%) were imported from abroad. The pH, moisture content %, ash content % and salt saturation % of the salted hides were determined. In the salted hides, the pH values of all samples (pH 6-9) and moisture content (49-66%) in 28% of the samples were found to be appropriate for bacterial growth. It was determined that ash content in 25% (10-14%) of the salted hides and salt saturation in 22% (65-84%) of the salted hides were suitable for the growth of mesophilic bacteria. Despite the salt-curing of hides, proteolytic and lipolytic mesophilic bacteria were isolated from the hides in high numbers. Proteolytic and lipolytic extremely halophilic bacteria were observed in the most samples of salt and salted hides. These bacterial counts were 102-10 4 c.f.u./g in the salt samples whereas they were 10 2-106 c.f.u./g in the salted hides. Although proteolytic and lipolytic mesophilic bacteria were 105-108 c.f.u./g in 97% of the soaked hide samples, they were 105-106 c.f.u./ml only in 42% of the soak liquors. In conclusion, it was determined that this hide preservation method was not adequate to inactivate bacterial activity. Hence, bacterial activity was high in the salted and soaked hides and also the concentration of antibacterial agents used in the soaking process was not sufficient. It is believed that eliminating of these problems will provide to increase hide quality.